Broadening the scope of open innovation: past research, current state and future directions. (1st January 2010) - van de Vrande, Vareska; Vanhaverbeke, Wim; Gassmann, Oliver
In this first paper of the special issue, we identify some trends in open innovation research by analysing how the literature on this topics has evolved since the introduction of the concept in 2003. Research on open innovation has been mushrooming ever since and the scope has been broadened in different directions. Researchers also started to analyse open innovation at different level of analysis from the individual actors in organisations to ecosystems and national innovation systems. Despite the vast growth in research on open innovation, we identified several directions for further research: open innovation research should be linked to other management areas such as marketing, HRM, change management, etc. In addition, our understanding of open innovation could be improved if the recently developed insights could be related to the existing management theories.